I thought we were vibin': A qualitative exploration of sexual agency and consent in young people. (October 2021) - Schobert, Kelsey; Cooper, Spring; Fries, Noelle; Sonia Chervillil, Mary
While there is much attention paid to the connection between social boundaries and consent, the relationship between consent literacy and sexual agency has not yet been explored. This qualitative analysis, which is part of a larger mixed-methods study, sought to explore the relationship between consent literacy and sexual agency in young people. Participants ( n = 18) were recruited from nonprofit organizations and were asked to complete a 30–40 minutes semi-structured interview and two questionnaires. Through our grounded theory approach to the analysis of the interviews, we identified three overarching themes and several sub-themes. The main themes were as follows: (1) Young people develop a broad understanding of sexual agency and consent through various social and environmental influences; (2) Most of consent is conceptualized through non-verbal cues ("vibes"), prior communication, and past experience with the person; (3) There are notable differences in demonstrable sexual agency between males and females and non-binary individuals, and between individuals participating in heterosexual versus queer sex acts in establishing and negotiating consent. These results provide preliminary evidence that sexual agency and consent literacy share similarities as they are being used in practice during sexual interactions. Further research is needed to deepen our understanding of how these constructs are related in order to improve levels of consent literacy.